2001
DOI: 10.1021/om010481a
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Steric Control of Stereoselective Olefin Binding in Cyclopentadienyl Complexes of Rhenium:  An Application of de Novo Ligand Design

Abstract: Gladysz has demonstrated that the [(η 5 -C 5 H 5 )Re(NO)(PPh 3 )] + fragment can stereoselectively bind prochiral olefins. The origins of selectivity are thought to be rooted in the steric interaction between the substituent on the olefin and ligands on the Re. Using Brown's ligand repulsive energy methodology, we have verified that stereoselectivity toward prochiral R-olefins in [(η 5 -C 5 H 5 )Re(NO)(PPh 3 )] + can be understood in terms of a steric argument. Using molecular mechanics, we examine how the fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…The relative free energies of 1 ′ and 2 ′ and their rotational isomers 1R ′ and 2R ′ are in the same order as suggested by Gladysz and co-workers, namely 1 ′ < 2 ′ < 1R ′ < 2R ′, using either B3LYP or M06 functionals. Our results are in accord with a previous computational study conducted by White et al, who carried out a conformational search of the same complexes . Comparisons of the selected structural parameters and the free energy values of the four isomers of PPh 3 and PMe 3 complexes are presented in Tables and respectively.…”
Section: Resultssupporting
confidence: 90%
“…The relative free energies of 1 ′ and 2 ′ and their rotational isomers 1R ′ and 2R ′ are in the same order as suggested by Gladysz and co-workers, namely 1 ′ < 2 ′ < 1R ′ < 2R ′, using either B3LYP or M06 functionals. Our results are in accord with a previous computational study conducted by White et al, who carried out a conformational search of the same complexes . Comparisons of the selected structural parameters and the free energy values of the four isomers of PPh 3 and PMe 3 complexes are presented in Tables and respectively.…”
Section: Resultssupporting
confidence: 90%
“… While less frequently applied, this descriptor-guided screening approach has been employed to identify ways to improve catalyst stability (i.e., by strengthening the bond with the mostly weakly bound ligand) without affecting activity . When sterics are believed to play an essential role, this screening and iterative design process has been accelerated by using molecular-mechanics-derived quantities such as the ligand repulsion energy to predict relative stereoselectivity of substrate binding …”
Section: Statistical Modeling For Transition-metal Chemistrymentioning
confidence: 99%
“…443 When sterics are believed to play an essential role, this screening and iterative design process has been accelerated by using molecular-mechanics-derived quantities such as the ligand repulsion energy 402 to predict relative stereoselectivity of substrate binding. 444 Exploiting linear free energy relationships (LFERs) between activation energies and reaction energies or selectivities as well as relating energies to a specific descriptor is a special example of descriptor-based design. This approach has been most widely applied and popularized in heterogeneous catalysis, where it has been shown that bulk metal alloy reaction energetics are closely related to descriptors (e.g., the d-band center), enabling estimation of overall optimal activity (i.e., a maximum in a volcano plot) from a single descriptor.…”
Section: Data Mining Structures For Chemical Trendsmentioning
confidence: 99%
“…Gillespie et al examined the steric interplay between ligands on the Re atom and the substituent on the prochiral alpha-olefin (R 1 and R 2 ) in order to rank the relative importance of the size of ligands in terms of binding selectivities. [61,62] The authors concluded that the size of the phosphine is more important than the size of the cyclopentadienyl ring in determining which face of the prochiral olefin is bound by an enantiomerically pure organometallic Lewis acid. The study is a part of the so called de novo ligand design pyramid, where sterics and energetics of the system are studied using different levels of computational theory, from MM to ab initio passing by SEQM and QM.…”
Section: The Ligand Repulsive Energy Methodsmentioning
confidence: 99%